PERSONALISM: RELEVANCE OF NIKOLAS LOSSKY PHILOSOPHY - Суходуб, Т. Д. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
Personalism is analyzed as an example of Lossky creativity and develops a "new" humanism. It is proved that personalism creates a doctrine that allows to overcome the historical development of the extreme ideologies of individualism and collectivism, offering a fundamentally different understanding of the individual, society and culture.